Qualifying the relationship between sequence conservation and molecular function - Cooper, Gregory M.; Brown, Christopher D.

(untitled) (Genome Research, 2008)
Quantification of evolutionary constraints via sequence conservation can be leveraged to annotate genomic functional sequences. Recent efforts addressing the converse of this relationship have identified many sites in metazoan genomes with molecular function but without detectable conservation between related species. Here, we discuss explanations and implications for these results considering both practical and theoretical issues. In particular, phylogenetic scope influences the relationship between sequence conservation and function. Comparisons of distantly related species can detect constraint with high specificity due to the loss of conserved neutral sequence, but sensitivity is sacrificed as a result of functional changes related to lineage-specific biology. The strength of natural selection operating on functional sequence is also important. Mutations to functional sequences that result in small fitness effects are subject to weaker constraints. Therefore, particularly when comparing highly divergent species, functional sequences that are degenerate or biologically redundant will be prone to turnover, wherein functional sequences are replaced by effectively equivalent, but nonorthologous counterparts. Finally, considering the size and complexity of metazoan genomes and the fact that many nonconserved sequences are associated with sequence-degenerate, low-level molecular functions, we find it likely that there exist many biochemically functional sequences that are not under constraint. This hypothesis does not lead to the conclusion that huge amounts of vertebrate genomes are functionally important, but rather that such “functionality” represents molecular noise that has weak or no effect on organismal phenotypes.